Error Analysis of Written English Composition: A Case of Basic Level Students - Neupane, Ram Nath (Tribhuvan Journal, 2023)
Error analysis is an important branch of applied linguistics which deals with errors committed by second or foreign language learners. The present article is about error analysis that aims to investigate the frequency, types and causes of errors committed by basic level students. To accomplish the objectives, the researcher adopted positivist philosophical approach and survey research design. The researcher collected the data from two schools of Palpa and two schools of Rupandehi consisting ten students from each school. Writing composition was the main tool for data collection and the collected data were categorized into different categories such as verb tense, subject verb agreement, inappropriate use of article, wrong use of preposition. The frequency of occurrence of errors and their causes were analyzed. The findings of the study highlight that the most of basic level students commit grammatical errors in sub-verb agreement and they are caused due to intralingual as well as interlingual factors. This study can play a pivotal role for improving writing skills of students.